Four new species of Alysiinae (Hymenoptera: Braconidae) and a new record from Colombia - DIX, OSCAR (Revista Colombiana de Entomología, 2010)
Four new species of the subfamily Alysiinae are described from Colombia: Alysiasta lunae sp. n., Idiasta dixi sp. n., Tanycarpa edithae sp. n. and T. sarmientoi sp. n. A taxonomic key to separate the species of the genus Alysiasta in the New World is provided. Additionally, morphological variation reported for the species I. delicata and A. pilopedibus is broadened and evidence supporting the transfer of A. pilopedibus to the genues Gnathopleura is provided.